1988
DOI: 10.1093/infdis/158.2.360
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Outer Membrane Proteins of Nontypable Haemophilus influenzae in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Five individual colonies of Haemophilus influenzae were isolated from each of one to three cultures of sputum collected from 18 patients with chronic obstructive pulmonary disease (COPD). The isolates were studied to investigate whether the major outer membrane proteins (MOMPs) changed during persistence. The relationship between isolates was analyzed by fingerprinting their chromosomal DNA. The fingerprints of eight strains (isolated from eight patients) with various MOMP compositions were different, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 28 publications
4
97
0
Order By: Relevance
“…Chromosome fingerprint analysis of NTHi isolates from patients with COPD demonstrated genetic diversity [4]. However, analysis of genetic types by multi-locus enzyme electrophoresis suggested that isolates from persistent carriage or chronic infections are more diverse than isolates from acute infections [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosome fingerprint analysis of NTHi isolates from patients with COPD demonstrated genetic diversity [4]. However, analysis of genetic types by multi-locus enzyme electrophoresis suggested that isolates from persistent carriage or chronic infections are more diverse than isolates from acute infections [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, analysis of genetic types by multi-locus enzyme electrophoresis suggested that isolates from persistent carriage or chronic infections are more diverse than isolates from acute infections [5]. The major outer-membrane protein (OMP) profile of chronic bronchitic isolates varies in the electrophoretic mobility of proteins P2 (protein b, c) and P5 (protein d) [4]. Furthermore, sequence analysis of the heatmodifiable protein, P5, from five isolates and their variants from chronic bronchitics, has identified four hypervariable regions that are proposed to be surfaceexposed and subject to the immune pressure of the host [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that a major protein of 37 to electrophoretic mobility due to minor differences in its amino acid composition (14,32). That the major 37-to 40-kDa protein band was P2 was confirmed by immunoblotting using a guinea pig anti-P2 antiserum.…”
Section: Methodsmentioning
confidence: 94%
“…To remove any potential E. coli antibodies that may have cross-reacted with NTHi, sera were pre-absorbed with E. coli prior to flow cytometry as previously described. 40 NTHi-289 was grown as previously described, 16 harvested and washed twice with sterile PBS by centrifugation (400 g, 10 min at room temperature). The bacterial cell pellets were subsequently incubated for 1 h at 37°C with 200 μl of pre-adsorbed sera from the immunized rats, which had been diluted 1:50 in PBS.…”
Section: Methodsmentioning
confidence: 99%